2018
DOI: 10.1109/led.2017.2772865
|View full text |Cite
|
Sign up to set email alerts
|

Negative Differential Resistance and Steep Switching in Chevron Graphene Nanoribbon Field-Effect Transistors

Abstract: Ballistic quantum transport calculations based on the non-equilbrium Green's function formalism show that field-effect transistor devices made from chevron-type graphene nanoribbons (CGNRs) could exhibit negative differential resistance with peak-to-valley ratios in excess of 4800 at room temperature as well as steepslope switching with 6 mV/decade subtheshold swing over five orders of magnitude and ON-currents of 88 µA µm −1 . This is enabled by the superlattice-like structure of these ribbons that have large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Early research largely focused on the potential role of GNRs in field-effect transistors (3,4), revolving around tailoring the size of their bandgap through width, edge, and heteroatom engineering (2,(5)(6)(7), as well as the formation of heterojunctions through copolymerization (5,8). Recently, the design of ever more intricate GNR structures has opened new avenues of exploration, including topics such as negative differential resistance (9)(10)(11)(12), spintronics (13,14), magnetism (15)(16)(17)(18)(19)(20), and quantum information processing (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Early research largely focused on the potential role of GNRs in field-effect transistors (3,4), revolving around tailoring the size of their bandgap through width, edge, and heteroatom engineering (2,(5)(6)(7), as well as the formation of heterojunctions through copolymerization (5,8). Recently, the design of ever more intricate GNR structures has opened new avenues of exploration, including topics such as negative differential resistance (9)(10)(11)(12), spintronics (13,14), magnetism (15)(16)(17)(18)(19)(20), and quantum information processing (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1974, Aviram and Ratner firstly designed a rectifier based on a single organic molecule [1], then the era of molecular devices was coming. Many important breakthroughs have been achieved in molecular devices already [2][3][4][5][6][7][8]. By means of external electric field, deformations of the molecular and light incident, many intriguing properties have been acquired in the past years [9][10][11], such as negative differential resistance (NDR) [12][13][14][15][16][17][18][19][20][21], molecular rectification [1,[22][23][24][25], molecular switch [17,[26][27][28], and conductance enhancement [29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence suggests C-GNRs as promising materials for applications in organic electronics and photovoltaics . Several other works have dealt with the synthesis of C-GNR. Some studies have shown that C-GNRs share interesting properties that arise in different carbon allotropes while presenting other unique features. , Finally, possible applications of C-GNRs in heterojunctions have also already been reported . However, so far, the literature lacks the theoretical description of its electronic and transport properties.…”
Section: Introductionmentioning
confidence: 99%